2011
DOI: 10.1530/eje-10-0823
|View full text |Cite
|
Sign up to set email alerts
|

Growth retardation in untreated autosomal dominant familial neurohypophyseal diabetes insipidus caused by one recurring and two novel mutations in the vasopressin-neurophysin II gene

Abstract: Objective: Autosomal dominant familial neurohypophyseal diabetes insipidus (adFNDI), a disorder caused by mutations in the vasopressin (AVP)-neurophysin II (NPII) gene, manifests gradually during early childhood with progressive polyuria and polydipsia. Patients are usually treated with synthetic AVP analog. If unlimited access to water is provided, prognosis is usually good even in the absence of specific treatment.In this study, we describe three families with adFNDI, in which growth failure was a prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Theoretically, plain MRI of the posterior pituitary reveals short T1 and high-intensity signals in normal individuals, while such signals are absent in patients with FNDI; however, a study of 79 patients with CDI with a median follow-up of 1.5 years (0.2-7.5 years) demonstrated that posterior pituitary MRI hyper-intensity signals disappeared in 6% of the patients (9). Thus, CDI cannot be excluded based on MRI alone (10).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Theoretically, plain MRI of the posterior pituitary reveals short T1 and high-intensity signals in normal individuals, while such signals are absent in patients with FNDI; however, a study of 79 patients with CDI with a median follow-up of 1.5 years (0.2-7.5 years) demonstrated that posterior pituitary MRI hyper-intensity signals disappeared in 6% of the patients (9). Thus, CDI cannot be excluded based on MRI alone (10).…”
Section: Discussionmentioning
confidence: 98%
“…This relatively high rate of mental retardation may result from the stress placed on the hypothalamus-pituitary axis due to excessive water consumption, which causes a persistent chronic hyperosmotic state, leading to anorexia, insufficient energy supply and impeded developmental processes (9). Due to the risk of developmental disorders, early intervention with medications, such as desmopressin acetate is essential to achieve good clinical outcomes (9). This further highlights the need for early diagnosis and symptoms prediction, which requires careful cataloguing of FNDI genetic components.…”
Section: Discussionmentioning
confidence: 99%
“…It may very well be present at birth but difficult to recognize. Failure to thrive in infancy may be the presenting sign, and inappropriate fluid restriction may be advised [15], as was done in our case. However, once the child became old enough to have free access to water, growth improved, so that auxological parameters were within normal limits by the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Growth retardation and delayed bone age are commonly reported in patients with central DI with an incidence of 20-35 %, and effectively corrected by desmopressin treatment [22]. However, some patients with unlimited and unrestricted fluid intake can thrive normally, which causes a difficulty in creating a clear genotype-phenotype correlation [23]. Nevertheless, in the present report, earlier age of onset of symptoms in family B can be a predictive clue in determining the severity of the mutation (p.G45C) as evidenced by the molecular studies mentioned previously.…”
Section: Discussionmentioning
confidence: 99%